: La Resolución No. 01 – 2016 y la afectación al principio de presunción de inocencia - Medina Garces, Gabriela Yosua (2023)
The reasonable doubt regarding the constitutionality that is accused relates to Resolution No. 001-2016 issued by the National Court of Justice, on March 16, 2016 and published in the Supplement to the Official Gazette No. 739, dated March 22, 2016. April 2016, the referred regulation is of constitutional relevance as it is the means to guarantee due process in the stage of execution of the sentence. The quantitative approach to research is one of the main tools for collecting information and studying a topic. This technique is designed to obtain objective, precise and verifiable information. This is accomplished by using a set of statistical techniques to collect data and then analyze it. This approach is used to better understand the interactions between variables. The goal is generally to find a relationship between variables, such as age and behavior. e concludes that the resolution mentions that the State must fulfill its obligation to protect the victims and the defendants, guaranteeing due process and legal security, among others. However, when examining the previous considerations made by the Court to approve it, it can be seen that there are innumerable interpretations that challenge the principle of progressivity of rights, which in turn leads to the violation of the right to legal certainty, to a effective protection and, above all, to the presumption of innocence. Keywords: resolution; principle of innocence; effective judicial protection; legal security